Decolorization of Reactive Red 159 by a consortium of photosynthetic bacteria using an anaerobic sequencing batch reactor (AnSBR). Issue 4 (21st April 2018) - Srisuwun, Aungkana; Tantiwa, Nidtaya; Kuntiya, Ampin; Kawee-ai, Arthitaya; Manassa, Apisit; Techapun, Charin; Seesuriyachan, Phisit
ABSTRACT: This experiment aimed to decolorize Reactive Red 159 using a high potential of a consortium of purple nonsulfur bacteria (PNSB) with an application of response surface methodology through a central composite design in open system. The three factors of hydraulic retention time (HRT), sludge retention time (SRT) and dye concentration were applied to the design. The decolorization was operated in an anaerobic sequencing batch reactor until the system reached to a pseudosteady state for 30 cycles in each experiment. The optimal condition was 6, 500 mg/L of Reactive Red 159 concentration with 20 days of SRT and 8 days of HRT, achieving dye effluent of 142.62 ± 5.35 mg/L, decolorization rate of 264.54 ± 7.13 mg/L/h and decolorization efficiency of 97.68 ± 0.74%. The results revealed that PNSB efficiently decolorized the high concentration of Reactive Red 159 and they were a high potential of microorganisms for dyes contaminated wastewater treatment.